A suitable marking method to achieve lateral margin negative in endoscopic submucosal dissection for undifferentiated-type early gastric cancer - Yoshimizu, Shoichi; Yamamoto, Yorimasa; Horiuchi, Yusuke; Yoshio, Toshiyuki; Ishiyama, Akiyoshi; Hirasawa, Toshiaki; Tsuchida, Tomohiro; Fujisaki, Junko (Endoscopy International Open, 2019)
Background and study aims Delineating undifferentiated-type early gastric cancer (UD-type EGC) from noncancerous areas is difficult. Therefore, the lateral margin negative (LM−) resection rate of endoscopic submucosal dissection (ESD) is lower for UD-type EGC than for differentiated-type EGC. This study aimed to retrospectively evaluate the effectiveness of the marking methods with circumferential biopsies in ESD for UD-type EGC.Patients and methods We analyzed the clinical outcomes of ESD in 127 patients with UD-type EGC between April 2013 and 2017. We performed diagnostic delineation of cancerous areas using magnifying endoscopy with narrow-band imaging, and four or more circumferential biopsies approximately 5 mm apart from the estimated lesion border were obtained to confirm noncancerous areas. The markings were placed on the circumferential biopsy scars, and a mucosal incision line was made outside the markings. Results Median size of the tumors and ESD specimens was 12 and 35 mm, respectively. En-bloc resection rate was 100 % (127/127), and LM− and curative resection rates were 97.6 % (124/127) and 80.3 % (102/127), respectively. Circumferential biopsy in preoperative esophagogastroduodenoscopy has successfully identified the misdiagnosis of cancerous areas of four patients (3.2 %), with three (2.4%) achieving LM− resection. LM + resection was pathologically identified in three patients (2.4 %), with all undergoing non-curative resection due to > 20-mm tumor. The proportion of patients with the shortest distance ≥ 5 mm from the lesion edge to the specimen edge was 88.2 % (112/127).Conclusion Our marking methods with circumferential biopsies may reduce LM + resections in ESD for UD-type EGC.